Analysis of potential plant as bioindicator for assessing heavy metals in drinking water - Noraishah binti A Majid (Kulliyyah of Science, International Islamic University Malaysia, 2017)
Pollution by organic and inorganic toxic substances has raised public and environmental concern globally. Due to rapid growth of world population along with excessive industrial development, this situation worsens. Non-essential heavy metals deteriorate biological functions in human and other living organisms. Biomonitoring, which use biological response to assess environmental changes, is one of the approaches that are getting more attention recently. Plant bioindicator offers huge advantages over conventional water quality analysis. Other than cheap, easy to apply and give rapid results, people in the rural area can apply this method to monitor water quality without the need of modern equipment and technical expertise. In this study, P. radula and P. sarmentosum were identified as the suitable plant bioindicators for selected non-essential heavy metals (As, Cd, Cr, Hg, Pb, Ni and Ag) detection, conferring a new hope for monitoring the safety of drinking water consumption. Both species were chosen as they gave the fastest, consistent and visible morphological changes (wilting, chlorosis and appearance of dark spots) within 6 h of metal treatment. Effects of heavy metals on the physiology and biochemical contents of both plant species were undertaken to understand the occurrence of the morphological changes observed. Young leaves were treated with different concentrations of metal solution (according to the National Drinking Water Guideline), along with controls. Elevated metal concentration in treatment solution significantly prompted an increased accumulation of metal ions in the leaf tissues. Meanwhile, total protein, chlorophylls as well as low molecular thiols contents (cysteine, GSH and GSSG) decreased as metals accumulation increased. However, PC2 production was induced in the metal-treated leaves, in comparison to the control. Based on these findings, it is postulated that heavy metals might interfere with the metabolic processes of plant cells, which was reflected from the morphological changes exhibited by P. radula and P. sarmentosum leaves. This new finding was promising, as it demonstrated that plants could be used for heavy metals biomonitoring for the safety of drinking water.